2020
DOI: 10.24036/ekj.v2.i1.a108
|View full text |Cite
|
Sign up to set email alerts
|

Development of Discovery Learning Based E-Module on Buffer Solution Topic for Class XI Senior High School (SMA/MA)

Abstract: The purpose of this study is to produce a discovery learning based e-module on buffer solution topic for Class XI Senior High School (SMA/MA). The type of research used is Research and Development using 4-D models with 4 stages, namely: (1) define, (2) design, (3) develop and (4) disseminate. This e-module was validated by 2 Chemistry lecturer from FMIPA UNP and 3 Chemistry teachers at Pertiwi 1 Padang High School, while the practicality test was carried out by 2 chemistry teachers and 26 students of class XII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The development model used to develop elearning with this buffer is a 4D model (a 4D model developed by Thiagarajan et al step). , development (development phase) and diffusion (diffusion phase) [24,25,26]. However, this study is limited to the development stage.…”
Section: Methodementioning
confidence: 99%
“…The development model used to develop elearning with this buffer is a 4D model (a 4D model developed by Thiagarajan et al step). , development (development phase) and diffusion (diffusion phase) [24,25,26]. However, this study is limited to the development stage.…”
Section: Methodementioning
confidence: 99%
“…Education in Indonesia is also one of the areas affected by the Covid-19 pandemic. Due to interaction restrictions, the Indonesian Ministry of Education also issued a policy to dissolve schools and replace the teaching and learning process with an online system [23] .…”
Section: Define Stage 311 Front-end Analysismentioning
confidence: 99%
“…In developing teaching material based on PAKEM, there were several stages of development carried out by researchers, including potential and problems, data collection, product design, design validation, design revision, and preliminary field testing (Ilahiyah, Asih & Pamungkas, 2019). Furthermore, Dinata & Zainul (2020) concluded that based on the validation results, the score obtained was 0.92 with a very valid category. In addition, this e-module also had a score of 0.94 for teacher response and 0.83 for student response.…”
Section: Introductionmentioning
confidence: 99%